Literature review: The Effect of Using Non-Herbal Panty Liners on Abnormal Vaginal Discharge in Adolescent Girls - Sofiyah, Shohebatuz; Andarwulan, Setiana (Future Science, 2021)
Teenagers are very vulnerable to experiencing problems such as vaginal discharge and because of that teenage girls often wear panty liners outside of their menstrual period. Improper use of panty liners will make vaginal discharge abnormal. Therefore, this literature review aims to find out how to use non-herbal panty liners so that they can cause abnormal vaginal discharge. This research usesliterature review with data sources from the PubMed, Research Gate, and Google Scholar databases with a range of 2018-2021. The results of this literature review contained 4 journals which stated that the effect of using panty liners could cause vaginal discharge but under normal conditions and 4 journals also stated that abnormal vaginal discharge was caused by panty liners. It can be concluded that abnormal vaginal discharge is caused by a different way of using panty liners and the lack of information about using panty liners properly.